The Right to Gender Equality in Tourism in the Context of Pandemic COVID-19 in the Canton Riobamba, Ecuador - CEJAS, Mercedes NAVARRO; CEJAS MARTINEZ, Magda Francisca; ALDÁZ, Silvia H. M.; MENDOZA VELAZCO, Derling José (Journal of Environmental Management and Tourism, 2021)
The main objective of this research is to analyze the right to gender equality in tourism in the context of the COVID-19 pandemic in the canton of Riobamba, Ecuador. A methodology was used within the multi-layered modality. The study design was DEXPLIS, based on grounded theory and the inductive-deductive and analytical - synthetic methods were implemented by means of a descriptive analysis. A checklist was applied for data collection survey of a sample of women workers in the tourism sector and it was determined that in the context of the pandemic that humanity is going through, women as a vulnerable group will not only have significant impacts that compromise their empowerment but also that in addition, Ecuador does not have sustainable legal measures to address the sensitive realities that have led to the health crisis.